(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2021)
This contribution is based on an article published in 2010 by D’ARS magazine about media activism art performances going on in Italy in those years, which referred to experiences, critical debate and tools around the web, and relating to hacktivism and social hacking. The expression "net.art" applies to many of the works dealt with. Among the most frequent practices, we have détournement, the irreverent dadaist gesture against the establishment apparatus, which aims to downsize its power and give way to imagination. The contribution retraces those experiences starting from netartists 0100101110101101.org and the Conflitto di Tirana performance. It goes back to works by Les Liens Invisible in the field of artivism, and works by AOS – Art Is Open Source - whose focus is on reappropriation of languages and tools.